The ADAM12 is upregulated in synovitis and postinflammatory fibrosis of the synovial membrane in patients with early radiographic osteoarthritis - Kerna, Irina; Kisand, Kalle; Suutre, Siim; Murde, Maret; Tamm, Ann; Kumm, Jaanika; Tamm, Agu (Joint, bone, spine : revue du rhumatisme, 2014)
To investigate the possible association between ADAM12 (disintegrin and metalloproteinase domain12) expression in the synovium and the histological synovitis of patients with radiographic knee osteoarthritis (rKOA). The synovial biopsy samples were harvested from 44 subjects with chronic knee complaints during arthroscopy. In all subjects, the radiographs of both knee joints were performed for rKOA assessment. Histological features of synovitis were graded 0–3 in synovial samples. Messenger RNA (mRNA) of two ADAM12 splice variants [ADAM12-S(hort) and ADAM12-L(ong)] and the identical region for both–ADAM12-B(oth) were measured by real-time reverse transcription-PCR in all synovial samples (TaqMan® gene expression assay). Immunohistochemical staining of the synovial membrane with ADAM12 antibody was performed in 42 subjects. ADAM12 mRNA was expressed in all synovial samples, whereas the main part of overall expression consisted of its long isoform (ADAM12-L). ADAM12 protein expression was detected in 80% of the synovial samples and correlated with mRNA expression (ρ=0.30, P<0.05). The expression of ADAM12 mRNA and protein in synovium correlated with the severity of histological synovitis (ρ=0.28, P<0.05 for ADAM12-B mRNA, R2=0.20, P<0.05 for ADAM12 protein). Out of several features of synovitis the expression level of both splice variants correlated only with the grade of fibrosis in the synovium (ρ=0.30, P<0.05 for ADAM12-L and ρ=0.33, P<0.05 for ADAM12-S). ADAM12 is upregulated in the synovial tissue during synovitis on mRNA and protein level. We suggest that ADAM12 could be implicated in the development of KOA-associated synovitis, especially in the occurrence of postinflammatory fibrosis.